Acoustic roughness analysis of a diesel engine noise. (2017) - Mao, Jie; Zhu, L.; Wang, Xu; Peng, H.
A modified Aures roughness algorithm (MARA) is proposed, which considers sound transfer functions of the concha, middle ear, and inner ear to improve the algorithm integrity and human auditory perception. A MARA-based method is implemented to simulate, optimise, and evaluate the acoustic roughness of a diesel engine noise. The finite-element engine components are validated by modal frequency test. Then, the normal vibration velocities and structural radiated noise of the block surface are obtained by flexible multi-body dynamic theory and boundary element method. The sound power levels and roughness of the radiated noise are calculated. Finally, the structure-borne noise is optimised to reduce roughness, which has validated the modified Aures roughness algorithm.